INVESTIGASI MIKROSTRUKTUR DAN KEKERASAN MATERIAL GEARBOX TRAKTOR TANGAN DENGAN METODE PENGECORAN LOGAM - Kusnowo, Roni; Nadi, M. Rizki Gorbyandi; Hermana, Gita Novian; Siswanto , Ari; Nahrowi , Muhammad; Ruskandi , Cecep; Gemilang , Yun (Jurnal Rekayasa Mesin, 2024)
Tractor gearboxes have become a crucial mechanization tool in the agricultural industry in Indonesia. However, in practice, many of the hand tractor gearboxes available are still imported. Therefore, research is needed to produce hand tractor gearboxes to support domestic industry self-sufficiency. The gray cast iron hand tractor gearbox is produced using a metal casting process with sand molds. The material resulting from this metal casting process has a composition of 3.249 wt.% C, 1.757 wt.% Si, 0.6 wt.% Mn for the first batch, 3.153 wt.% C, 1.568 wt.% Si, 0.624 wt.% Mn for the second batch, and 3.105 wt.% C, 1.932 wt.% Si, 0.560 wt.% Mn for the third batch. Based on microstructure analysis, the gray cast iron consists of 5% ferrite phase, 95% pearlite, and flake graphite type A with a size of 5. Brinell hardness testing resulted in hardness values of 152, 155, and 164 BHN for the gray iron for the first, second, and third batches respectively. The gray cast iron has a yield strength of 163, 172, and 176 MPa for each batch respectively. Meanwhile, the tensile strength of the gray cast iron from each batch is 285, 311, and 326 MPa